TEENAGE JEJUNOILEAL DIVERTICULOSIS - Shah, Syed Inamullah; Bashir, Eitezaz Ahmad; Hannan, Abdul; Sadiq, Attique; Baig, Mehreen (Journal of Ayub Medical College Abbottabad, 2013)
Presentation of jeujunoileal diverticulosis in young age is virtually unknown. It is associated with middle or old age. It is usually asymptomatic but may present with vague abdominal pain and episodic nausea, vomiting or diarrhoea. It can lead to complications like bleeding, perforation and obstruction. We had 3 cases of jejuno-ileal diverticulosis presenting in their teens. They had resection and anastomosis resulting in improved health. Keywords: Teenage, Jejuno-ileal, Diverticulosis